The Optimal Number of Oocytes Retrieved From PCOS Patients Receiving IVF to Obtain Associated With Maximum Cumulative Live Birth Rate and Live Birth After Fresh Embryo Transfer - Jia, Rui; Liu, Yuanyuan; Jiang, Rulan; Zhu, Xuli; Zhou, Liang; Chen, Peipei; Cao, Mingya; Zhao, Zhiming (Frontiers in Endocrinology, 2022)
Aims This study aims to determine the optimal number of oocytes retrieved so that patients with polycystic ovary syndrome (PCOS) receiving in vitro fertilization (IVF) can obtain the best cumulative live birth rate (CLBR) and live birth after fresh embryo transfer. Methods This is a retrospective study of 1,419 patients with PCOS who underwent their first IVF cycle at the Second Hospital of Hebei Medical University from January 2014 to December 2021. Multivariable regression analysis was performed to adjust for factors known to independently affect cumulative live birth aspiration. The number of oocytes retrieved to obtain the best cumulative live birth rate was explored through curve fitting and threshold effect analysis. The decision tree method was used to explore the best number of oocytes retrieved to achieve live birth in the shortest time. Results (1) The number of oocytes retrieved was found to be an independent protective factor for the cumulative live birth rate (OR = 1.09 (95% CI: 1.06, 1.12)). When the number of oocytes retrieved was less than 15, CLBR increased by 16% with each increase in the number of oocytes retrieved (OR = 1.16 (95% CI: 1.11, 1.22)); and when more than 15, CLBR tended to be stable. (2) Live birth after the first fresh embryo transfer was analyzed through a classification decision tree. For patients younger than 35 years old, those with less than 6 oocytes and those with 7–16 oocytes had a similar proportion of live births with fresh embryo transfer but higher than 16 oocytes (53.7% vs. 53.8% vs. 18.4%). Patients older than 35 years old had a similar proportion of live births with fresh embryo transfer (35.7% vs. 39.0%) to those younger than 35 years old, but the proportion of no live births after using up all embryos was higher than those younger than 35 years old (39.3% vs. 19.2%). Conclusions In PCOS patients, high CLBR can be obtained when the number of oocytes retrieved was 15 or more. The number of oocytes retrieved from 7 to 16 could achieve more chance of live birth after fresh embryo transfer.